OSTEOARHRITIS OF THE KNEE (GUIDELINE FOR TREATMENT) - Noverial Noverial (LLDIKTI Wilayah X, 2012)
As OA is associated with aging, the impact of this disease will continue to grow over the next decade. With no cure, physicians and patients alike attempt to control the pain, stiffness, and other adverse effects. Most of the treatments of OA address the symptoms rather than the cause of the disease. They have been targeted to decrease pain and inflammation while preserving independence and quality of life as much as possible. Presently OA has no cure, and physicians have little hope that a cure will be available shortly, treatment strategies focus on treating the disease symptoms with minimal side effects. Interestingly, physicians show a greater interest in more effective, safer drugs than a “super-drug” that would cure OA. OA is a major cause of pain and disability in the elderly. Pain caused by inflammation of bursae and cartilage, subchondral fracture, distention and instability of the capsule and cartilage, osteophyte formation, spasm of the muscle. Progression of this disease in the knee may take many years. Once established however, the joint may remain in a stable condition for many years. Triad at large; pain, disability and structural change.